2018
DOI: 10.1037/h0101821
|View full text |Cite
|
Sign up to set email alerts
|

Do you know him? Gaze dynamics toward familiar faces on a Concealed Information Test.

Abstract: Can gaze position reveal concealed knowledge? During visual processing, gaze allocation is influenced not only by features of the visual input, but also by previous exposure to objects. However, the dynamics of gaze allocation toward personally familiar items remains unclear, especially in the context of revealing concealed familiarity. When memorizing four pictures of faces on a short term memory task, participants' gaze was initially directed toward a personally familiar face, followed by a strong avoidance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 37 publications
2
19
1
1
Order By: Relevance
“…Previous familiarity studies that used eye tracking measurements detected fewer fixations with longer fixation durations when a familiar face was viewed (Nahari et al, 2019) and fewer areas of interest on the face when the participants were instructed to conceal their knowledge of familiarity (Millen & Hancock, 2019). With a memory task, familiar faces were less explored perhaps because they are easier to remember (Lancry-Dayan et al, 2018). In recent studies with different eye measurements, a longer OMI was found for microsaccades and for blinks when face stimuli were briefly presented and masked (Rosenzweig & Bonneh, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous familiarity studies that used eye tracking measurements detected fewer fixations with longer fixation durations when a familiar face was viewed (Nahari et al, 2019) and fewer areas of interest on the face when the participants were instructed to conceal their knowledge of familiarity (Millen & Hancock, 2019). With a memory task, familiar faces were less explored perhaps because they are easier to remember (Lancry-Dayan et al, 2018). In recent studies with different eye measurements, a longer OMI was found for microsaccades and for blinks when face stimuli were briefly presented and masked (Rosenzweig & Bonneh, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have focused on different aspects of gaze fixations; one study claimed that the first two fixations are critical for revealing familiarity (Schwedes & Wentura, 2019), and other studies suggested that fewer fixations and longer fixation durations are the key for familiarity (Millen & Hancock, 2019; Peth, Kim, & Gamer, 2013). In contrast, another study reported more fixations and longer fixation durations for familiar faces with a CIT paradigm (Nahari, Lancry-Dayan, Ben-Shakhar, & Pertzov, 2019); however, when participants had to memorize faces, familiar faces initially attracted their gaze, but later triggered fewer fixations and shorter fixation durations (Lancry-Dayan, Nahari, Ben-Shakhar, & Pertzov, 2018). Overall, the eye movement behavior in relation to face familiarity depended on the instructions given by the researcher.…”
Section: Introductionmentioning
confidence: 91%
“…However, they did not include the analysis of the eye movement paths and the facial region of interests in their studies. Lancry-Dayan et al recently explored in 2018 the possibility of detecting a subject's familiarity with other faces using machine learning techniques by demonstrating him or her four face photos in parallel [12]. They discovered that among the given four faces, subjects turn to fixated more on their familiar faces, followed by a tendency to move eyes away from it [12].…”
Section: Introductionmentioning
confidence: 99%
“…Lancry-Dayan et al recently explored in 2018 the possibility of detecting a subject's familiarity with other faces using machine learning techniques by demonstrating him or her four face photos in parallel [12]. They discovered that among the given four faces, subjects turn to fixated more on their familiar faces, followed by a tendency to move eyes away from it [12]. Furthermore, machine learning techniques can successfully leverage this behaviour and showed robust results among different individuals [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation